Diabetic foveal avascular zone: differences between high speed and high resolution scans - Pereira, Bruno (2022)
Diabetic retinopathy is one of the causes of the pathological increase of the Foveal Avascular Zone (FAZ) area and is assessable by optical coherence tomography angiography (OCTA). Even using the same equipment, different acquisition protocols may lead to different results. Aim of the study: To evaluate the differences in manual FAZ area measurements comparing two different OCTA acquisition protocols, High Speed (HS) versus High Resolution (HS).